2007
DOI: 10.1007/s10661-007-9919-4
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation composition and wet deposition temporal pattern in Central Serbia for the period from 1998 to 2004

Abstract: Bulk samples collected on a daily basis at three principal meteorological stations in central Serbia were analyzed on chloride (Cl(-)), nitrate (NO(3)(-)), sulfate (SO(4)(2-)), sodium (Na(+)), ammonium (NH(4)(+)), potassium (K(+)), calcium (Ca(2+)), and magnesium (Mg(2+)) in addition to precipitation amount, pH and conductivity measurements over the period 1998-2004. The data were subjected to variety of analyses (linear regression, principal component analysis, time series analysis) to characterize precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Although the deposition of K + from energy production and industrial plants has decreased in some European countries [ 255 ], that of K + from agricultural activities is very high in some developing countries, such as Brazil, reaching 55% of total K + deposition [ 256 ]. K + deposition linked to industrial and mainly agricultural activities can be higher than deposition from natural processes [ 257 , 258 ], such as sea spray [ 259 , 260 ]. The inputs of K + from atmospheric deposition have a determinant role in K + balances of forests, counteracting the loss of K + from leaching, which is favored by N deposition, due indirectly to soil pH decrease and soil degradation and directly to the competition with ammonium for the occupation of the exchangeable complex [ 261 , 262 ].…”
Section: Role Of K In Terrestrial Ecosystemsmentioning
confidence: 99%
“…Although the deposition of K + from energy production and industrial plants has decreased in some European countries [ 255 ], that of K + from agricultural activities is very high in some developing countries, such as Brazil, reaching 55% of total K + deposition [ 256 ]. K + deposition linked to industrial and mainly agricultural activities can be higher than deposition from natural processes [ 257 , 258 ], such as sea spray [ 259 , 260 ]. The inputs of K + from atmospheric deposition have a determinant role in K + balances of forests, counteracting the loss of K + from leaching, which is favored by N deposition, due indirectly to soil pH decrease and soil degradation and directly to the competition with ammonium for the occupation of the exchangeable complex [ 261 , 262 ].…”
Section: Role Of K In Terrestrial Ecosystemsmentioning
confidence: 99%
“…deposition of K from energy production and industrial plants has decreased in some European countries (Ruoho-Airola & Salminen, 2003). Some studies have observed that K deposition, linked to industrial and, frequently, agricultural activities, can represent a higher proportion than that from natural processes (Ferm & Hultberg, 1999;Golobocanin et al 2009) such as sea spray (Poor et al, 2006;Prathibha et al, 2010).…”
Section: Anthropogenic Impacts On the K Cycle K Fertilizersmentioning
confidence: 99%
“…The atmospheric deposition of K originates from natural processes such as sea spray (Appendix S1) but also from agricultural activities and human industrial activities such as fertilizer and cement production, petrochemicals, the steel industry, and coal combustion (Klumpp et al, 2002;Walker et al, 2003;Urban et al, 2012). In some areas human activities can contribute a higher proportion of K deposition than natural processes (Ferm & Hultberg, 1999;Golobocanin et al, 2009). However, we are far 57.7 x 10 9 t K (1,2) (1-2% of total soil K) 0.066 x 10 9 t K Plant available (in soil solution plus exchangeable) 57.7 10 9 t K (1,2) (1-2% of total soil K) nonexchangeable 3773-7662 x 10 9 t K (1,2)…”
mentioning
confidence: 99%
“…The availability of K in ecosystems also depends on K inputs via atmospheric deposition, which can originate both through natural processes and human and agricultural activities, such as energy production, transportation, construction-materials production and fertilization (Walker, Young, Crittenden & Zhang, 2003;Urban et al, 2012). Golobocanin, Zujic, Milenkovic & Miljevic (2009) demonstrated that human activities contribute a higher proportion of atmospheric deposition than natural processes. Jordi & Josep (2015) indicated that current levels of K fertilization and atmospheric deposition of K (0.066 × 10 9 t year -1 ) are very low compared with global available soil K (57.7 × 10 9 t).…”
Section: Increase Of Atmospheric Depositionmentioning
confidence: 99%